Spectrophotometric evaluation of color changes of esthetic brackets stored in potentially staining solutions - Medonça, Marcos Rogério de [UNESP]; Fabre, Aubrey Fernando [UNESP]; Goiato, Marcelo Coelho [UNESP]; Cuoghi, Osmar Aparacido [UNESP]; Martins, Lídia Pimenta [UNESP]; Verri, Ana Carolina Gonçalves [UNESP] (My University, 2011)
The purpose of this study was to evaluate, in vitro, the chromatic behavior of esthetic brackets stored in potentially staining solutions. The sample were divided into four groups according to the commercial brand and stored in four different solutions (distilled water, cola soda, coffee and mouthrinse) at 37°C for 14 days. Possible color changes measured according to the CIE L*a*b* color system with a spectrophotometer at five intervals of time after storage. The statistical analysis was carried out using ANOVA to 1%, Tukey's tests and decomposition of interactions with a significance level of 5%.The color changes were dependent on the solution, storage time and the brand of brackets. The largest color changes were observed in the G3, followed by G2, G1/G4. The esthetic brackets do not present satisfactory and stable chromatic behavior.

O objetivo deste estudo foi avaliar, in vitro, o comportamento cromático de braquetes estéticos armazenados em soluções potencialmente corantes. As amostras foram divididas em quatro grupos de acordo com a marca comercial e imersas em quatro soluções diferentes (água destilada, refrigerante à base de cola, café e enxaguatório bucal) a 37ºC, por 14 dias. As possíveis alterações de cor foram medidas de acordo com o sistema CIE L*a*b* por meio de um espectrofotômetro em cinco intervalos de tempo após armazenamento. A análise estatística foi conduzida usando ANOVA a 1%, testes de Tukey e decomposição das interações com nível de significância de 5%. As alterações de cores ocorreram conforme solução, tempo de armazenamento e marca dos braquetes. As maiores variações cromáticas foram observadas no G3, seguido por G2, G1/G4. Os braquetes estéticos não apresentam comportamento cromático estável e satisfatório.
Avaliação espectrofotométrica das alterações cromáticas de braquetes estéticos armazenados em soluções potencialmente corantes
Keywords: Color; Orthodontic brackets; Spectrophotometry; Cor; Braquetes ortodônticos; Espectrofotometria